EDUKASI KESEHATAN TENTANG BAHAYA INFEKSI MENULAR SEKSUAL (IMS) SEBAGAI UPAYA PENCEGAHAN PERGAULAN BEBAS PADA KALANGAN REMAJA DI SMAN 3 TANGERANG - Muchammad Reza Ghozaly; Fayza Maghfira Solachudin; Christhabel Vanessa Aurel Netanya (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
More than one million people are infected with sexually transmitted diseases every day and an estimated 499 million cases of sexually transmitted infections (STIs) occur each year. Adolescents and young adults (age 15-24 years) are the age group that is at the highest risk of contracting an STI. One of the efforts to prevent STIs in adolescents is to provide counseling about STIs. Adolescents and young adults (15-24 years) make up only 25% of the overall sexually active population but represent nearly 50% of new STI cases. Young people and adolescents are individuals most at risk for contracting STDs because at a young age, adolescents are disproportionately more susceptible. Indonesia is the fifth most at risk country for STIs in Asia. The total number of STI cases handled in 2018 was 140,803 out of 430 STI services. This shows that there is still a high incidence of STIs among adolescents. So it is necessary to carry out public health actions or interventions through the provision of health education. The form of community service activities is carried out by providing health education about sexually transmitted infections (STIs) as a means of providing information to adolescents. Activities carried out on teenagers at SMAN 3 Tangerang. The results of community service found that the majority of adolescent knowledge was lacking before counseling was carried out and the majority of adolescent knowledge was after counseling was given. The conclusion shows that there is an increase in adolescent knowledge after being given counseling compared to before counseling.